2018
DOI: 10.1101/423293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ANKRD31 regulates spatiotemporal patterning of meiotic recombination initiation and ensures recombination between heterologous sex chromosomes in mice

Abstract: Orderly segregation of chromosomes during meiosis requires that crossovers form between homologous chromosomes by recombination. Programmed DNA double-strand breaks (DSBs) initiate meiotic recombination. We identify ANKRD31 as a critical component of complexes of DSB-promoting proteins which assemble on meiotic chromosome axes. Genome-wide, ANKRD31 deficiency causes delayed recombination initiation. In addition, loss of ANKRD31 alters DSB distribution owing to reduced selectivity for sites that normally att… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…MEI4 is thus essential for assembly of RMMAI foci genome wide, while ANKRD31 contributes genome-wide but is more specifically essential for high-level enrichment at mo-2 regions. These results agree with findings of Tóth and colleagues, who further observed that REC114 but not IHO1 is essential for formation of blobs of the other RMMAI proteins (31).…”
Section: Both Rmmai Recruitment and Par Loop-axis Remodeling Require supporting
confidence: 93%
See 4 more Smart Citations
“…MEI4 is thus essential for assembly of RMMAI foci genome wide, while ANKRD31 contributes genome-wide but is more specifically essential for high-level enrichment at mo-2 regions. These results agree with findings of Tóth and colleagues, who further observed that REC114 but not IHO1 is essential for formation of blobs of the other RMMAI proteins (31).…”
Section: Both Rmmai Recruitment and Par Loop-axis Remodeling Require supporting
confidence: 93%
“…We found that the PAR was highly enriched for DSB-promoting factors REC114, MEI4, MEI1, and IHO1 [proteins essential for genomewide DSB formation (22-24, 29)] as well as ANKRD31, a REC114 partner essential for PAR DSB formation (30,31). All five proteins (hereafter RMMAI for simplicity) colocalized in several bright, irregular "blobs" for most of prophase I (Fig.…”
Section: A Distinctive Par Ultrastructure Rich In Pro-dsb Factorsmentioning
confidence: 93%
See 3 more Smart Citations